Reduced mechanism for combustion of hydrogen and methane with nitrogen chemistry - Azevedo, Pedro (2014)
A reduced chemical kinetic reaction mechanism that could be used in computational fluid dynamics (CFD) software was developed to describe the formation of nitrogen oxides and their subsequent destruction in hydrogen and/or hydrocarbon flames with or without seeding of nitrogen compounds. The research work presented here will describe the numerical work done with the application "CHEMKIN" in order to verify the quality of the reduced mechanism. The mechanism was validated through comparisons between computational data from a variety of different sources. In addition, numerical experiments were carried out to examine features of methane combustion in which the detailed mechanisms can be used to compare their response. The proposed reduced mechanism provides reasonable agreement with the studied detailed mechanisms, mainly in the species produced from the hydrocarbon oxidation process. Regarding the produced nitrogen species, the proposed reduced mechanism showed the same tendencies as the detailed mechanisms, but there is a need for a better agreement regarding the quantities.